Exercise, Vascular Stiffness, and Tissue Transglutaminase. Issue 2 (11th April 2014) - Steppan, Jochen; Sikka, Gautam; Jandu, Simran; Barodka, Viachaslau; Halushka, Marc K.; Flavahan, Nicholas A.; Belkin, Alexey M.; Nyhan, Daniel; Butlin, Mark; Avolio, Alberto; Berkowitz, Dan E.; Santhanam, Lakshmi
Abstract : Background: Vascular aging is closely associated with increased vascular stiffness. It has recently been demonstrated that decreased nitric oxide (NO)‐induced S‐nitrosylation of tissue transglutaminase (TG2) contributes to age‐related vascular stiffness. In the current study, we tested the hypothesis that exercise restores NO signaling and attenuates vascular stiffness by decreasing TG2 activity and cross‐linking in an aging rat model. Methods and Results: Rats were subjected to 12 weeks of moderate aerobic exercise. Aging was associated with diminished phosphorylated endothelial nitric oxide synthase and phosphorylated vasodilator‐stimulated phosphoprotein abundance, suggesting reduced NO signaling. TG2 cross‐linking activity was significantly increased in old animals, whereas TG2 abundance remained unchanged. These alterations were attenuated in the exercise cohort. Simultaneous measurement of blood pressure and pulse wave velocity (PWV) demonstrated increased aortic stiffness in old rats, compared to young, at all values of mean arterial pressure (MAP). The PWV‐MAP correlation in the old sedentary and old exercise cohorts was similar. Tensile testing of the vessels showed increased stiffness of the aorta in the old phenotype with a modest restoration of mechanical properties toward the young phenotype with exercise. Conclusions: Increased vascular stiffness during aging is associated with decreased TG2 S‐nitrosylation, increased TG2 cross‐linking activity, and increased vascular stiffness likely the result of decreased NO bioavailability. In this study, a brief period of moderate aerobic exercise enhanced NO signaling, attenuated TG cross‐linking activity, and reduced ex vivo tensile properties, but failed to reverse functional vascular stiffness in vivo, as measured by PWV.